Coronary MR angiography using image‐based respiratory motion compensation with inline correction and fixed gating efficiency. Issue 1 (20th March 2017) - Henningsson, Markus; Smink, Jouke; van Ensbergen, Gerald; Botnar, Rene
Abstract : Purpose: The purpose of this study was to evaluate a new inline motion compensation approach called image‐based navigation with Constant Respiratory efficiency UsIng Single End‐expiratory threshold (iNAV‐CRUISE) for coronary MR angiography (CMRA). Methods: The CRUISE gating technique was combined with iNAV motion correction and implemented inline for motion‐compensated CMRA on a 1.5 Tesla scanner. The approach was compared to conventional diaphragmatic navigator gating (dNAVG) in 10 healthy subjects. The CMRA images were compared for vessel sharpness and visual score of the right coronary artery (RCA), left anterior descending artery (LAD), left circumflex, and scan time. Results: The scan time was similar between the methods (dNAVG : 6:32 ± 1:09 vs. iNAV‐CRUISE: 6:58 ± 0:17, P  = not significant). However, the vessel sharpness of the RCA (dNAVG : 60.2 ± 10.1 vs. iNAV‐CRUISE: 71.8 ± 8.9, P  = 0.001) and LAD (dNAVG : 58.0 ± 8.0 vs. iNAV‐CRUISE: 67.4 ± 7.1, P  = 0.008) were significantly improved using iNAV‐CRUISE. The visual score of the RCA was higher using iNAV‐CRUISE compared to dNAVG (dNAVG : 3, 4, 3 vs. iNAV‐CRUISE: 4, 4, 3, P  < 0.01). Conclusion: The iNAV‐CRUISE approach out‐performs the conventional respiratory motion compensation technique in healthy subjects. Although scan time was comparable, the image quality was improved using iNAV‐CRUISE. Magn Reson Med 79:416–422, 2018. © 2017 The Authors Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance in Medicine. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.